Literature Study: Effect Of Protein Energy Intake And Exclusive Breast Milk History On Stunting - Aprianti, Rita (Jurnal EduHealth, 2022)
Incident toddler short , ordinary called as stunting, is one of the problem nutrition worldwide .In 2017 22.2% or around 150.8 million toddlers in the world are stunted. Nutritional Status Survey Toddler Integrated (SSGBI) conducted by Balitbangkes Ministry of Health Republic of Indonesia. This research aims to find out influence intake energy and protein as well history of exclusive breastfeeding to stunting incident . This research is studies literature that summarizes a number of relevant literature . _ Articles searched with using the Google Scholar database. After screening , 21 articles Fulfill terms and meet criteria . There is influence intake energy and protein and exclusive breastfeeding against stunting. Expected results this research will be one _ ingredient education and intervention nursing that can be applied in health services in prevent stunting